PENINGKATAN KAPASITAS DAN PEMBERDAYAAN INSTANSI MELALUI PELATIHAN DOCUMENT CONTROL DAN DIGITAL FILING SYSTEM - Amrina, Dania Hellin; Istiqomah, Intan; Nainggolan, Dedy Sunaryo; Hadyantari, Faizatu Almas; Umaroh, Rodhiah; Soewardi, Tiara Juniar; Yuliawati, Yuliawati (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2025)
Document management and filing systems are crucial elements in business operations, ensuring that documents are well-organized, secure, and easily accessible. The ‘Document Control and Filing System’ training was conducted over three days, from December 10–12, 2024, at éL Hotel Yogyakarta Malioboro. This training aimed to enhance participants' understanding of Document Control and Filing Systems and their implementation in the workplace. The training was attended by two participants from PT Cirebon Power in a private format, allowing for interactive discussions and in-depth material exploration.The training methods included presentations, discussions, case studies, and evaluations through pre-tests and post-tests. The evaluation results showed a significant improvement in participants' understanding of document management principles, filing classification, as well as data security and accessibility. Participants also gained more confidence in implementing a more systematic filing system in their companies.This training's implementation demonstrated that a discussion and case study-based approach effectively enhanced participants' competencies. With high enthusiasm and positive results, similar training programs can be further developed with a stronger focus on document digitalization and the implementation of technology in filing management.